Data and Privacy: Now you see me; New Model for Data Sharing; Modern Governance and Staticians. Issue 4 (3rd October 2014) - Smith, Sam
Abstract: Does data anonymisation work? The answer depends on who you talk to. But finding a way to preserve privacy while sharing valuable data is crucial to the future of our information society. Brian Tarran reports. Will the openPDS initiative at MIT solve the data privacy problem once and for all? Brian Tarran interviews researcher Brian Sweatt . Sam Smith writes: Policy-makers are hungry to take advantage of big data, but they must heed the warnings of statisticians when they say "enough is enough". Abstract : Does data anonymisation work? The answer depends on who you talk to. But finding a way to preserve privacy while sharing valuable data is crucial to the future of our information society. A new model for data sharing Will the openPDS initiative at the Massachusetts Institute of Technology solve the data privacy problem once and for all? Why modern governance needs statisticians Policy-makers are hungry to take advantage of big data, but they must heed the warnings of statisticians when they say "enough is enough".